2019
DOI: 10.9734/cjast/2019/v35i530203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Nutrient Management and Bio-regulators on Yield and Economics Attributes of Sprouting Broccoli {Brassica oleracea (L.) var. italica}

Abstract: The field experiment was conducted at Horticulture Farm, S.K.N. College of Agriculture, Jobner (Jaipur) during Rabi seasons of 2016-17 and 2017-18. The experiment consisted of thirty five treatment combinations including seven INM (100 per cent RDF through inorganic fertilizer, 75 per cent RDF through inorganic fertilizer + 25 per cent through FYM (5 t/ha), 50 per cent RDF through inorganic fertilizer + 50 per cent through FYM, 100 per cent RDF through FYM, 75 per cent RDF through inorganic fertilizer + 25 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In addition, farm yard manure improves the chemical, biological and physical characteristics of the soil, which facilitates optimal nutrient uptake by the plants and an increase in output. The results of present study are similar with Mohanta et al, (2018) [17] , Devi et al, (2018) [6] and Shankar et al, (2019) [20] . [11] , Yadav et al, (2020) [27] and Merentoshi et al, (2022) [15] .…”
Section: Yield Parameterssupporting
confidence: 92%
“…In addition, farm yard manure improves the chemical, biological and physical characteristics of the soil, which facilitates optimal nutrient uptake by the plants and an increase in output. The results of present study are similar with Mohanta et al, (2018) [17] , Devi et al, (2018) [6] and Shankar et al, (2019) [20] . [11] , Yadav et al, (2020) [27] and Merentoshi et al, (2022) [15] .…”
Section: Yield Parameterssupporting
confidence: 92%
“…Among different types of organic fertilizers treatment the highest marketable yield was recorded from T5 (19.242 t ha -1 ) followed by T4 (17.370 t ha -1 ), T3 (16.724 t ha -1 ), T2 (16.285 t ha -1 ), T1 (13.947 t ha -1 ) respectively and the lowest marketable weight of curd was observed from T0 (7.878 t ha -1 ) treatment (Figure 10). This finding showed that combined application of vermicompost with cowdung provided the best marketable yield which had also supported by Akter (2021) and (Ola et al, 2019).…”
Section: Marketable Yieldsupporting
confidence: 73%
“…Pooled data showed that the maximum net income of ₹ 2,45,840 was obtained in treatment T 8 followed by T 7 (90% of recommended dose of fertilizers + 5% drenching with jeevamrit @ 1.0 L m −2 + 5% foliar spray with jeevamrit) with net income of ₹ 2,34,757. According to Ola [ 39 ], the highest benefit cost ratio might be due to changes in the form of plant growth, yield and quality parameters. This improvement led to the proportional increase in yield and higher B:C ratio.…”
Section: Resultsmentioning
confidence: 99%